Accurate results in the clinical laboratory : a guide to error detection and correction - Dasgupta, Amitava, 1958-; Sepulveda, Jorge L. (Elsevier, 2019)
"Accurate Results in the Clinical Laboratory: A Guide to Error Detection and Correction, Second Edition, provides a comprehensive review of the factors leading to errors in all areas of clinical laboratory testing. This trusted guide addresses interference issues in all laboratory tests, including patient epigenetics, processes of specimen collection, enzymes and biomarkers"--Publisher's description